2019
DOI: 10.1007/s12032-019-1249-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes in patients with unresected stage III non-small cell lung cancer

Abstract: This study examined real-world clinical outcomes such as progression-free survival (PFS), time to metastasis (TTM), overall survival (OS), and health-related quality of life (HRQOL) in patients with unresected stage III non-small cell lung cancer (NSCLC) treated in the community setting. A retrospective review of medical records extracted from 10 US community oncology practices was conducted. Eligible patients were adults diagnosed with stage III NSCLC from 1/1/2011 to 3/1/2016 without evidence of surgical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 26 publications
(27 reference statements)
5
25
1
Order By: Relevance
“…This result suggests that MDT prolongs the length of survival for patients with stage III NSCLC. In addition, the median length of survival is approximately 22-24 months for patients with stage IIIA disease and 12-15 months for patients with stage IIIB disease [23][24][25][26]. The current study found the median survival was 39.4 months for patients with stage IIIA disease and 25.7 months for patients with stage IIIB disease.…”
Section: Plos Onementioning
confidence: 66%
“…This result suggests that MDT prolongs the length of survival for patients with stage III NSCLC. In addition, the median length of survival is approximately 22-24 months for patients with stage IIIA disease and 12-15 months for patients with stage IIIB disease [23][24][25][26]. The current study found the median survival was 39.4 months for patients with stage IIIA disease and 25.7 months for patients with stage IIIB disease.…”
Section: Plos Onementioning
confidence: 66%
“…Progression-free survival (PFS) and OS were also evaluated using Kaplan-Meier analyses. The PFS and OS results were published previously [14].…”
Section: Discussionmentioning
confidence: 99%
“…Median duration of treatment across all regimens in the third progression interval was 1.4 months. The median PFS from the first disease progression in the third progression interval was 3.1 months [14].…”
Section: Third Progression Intervalmentioning
confidence: 98%
See 2 more Smart Citations